Acacia caven cover on the pasture quality and microclimate in a silvopastoral system of central Chile - Lucero Ignamarca, Alejandro; Muñoz Sáez, Fernando; Cancino Cancino, Jorge; Sotomayor Garretón, Alvaro; Dube, Francis; Sáez Carrillo, Katia; Villaroel Muñoz, Arnoldo; Navarrete Torres, Mauricio (Instituto de Ecología, A.C., 2019)
The objective of this study was to determine the effect of different tree covers on the productivity and quality of the pasture and on specific microclimatic variables in an Acacia caven-based silvopastoral system. A trial that included four tree-cover treatments (0%, 30% - 40%, 50% - 60% and over 70%) was established in an experimental set-up with complete randomized blocks and three repetitions. In addition to the productivity and quality of the pasture, probes were used for the continuous measurement of soil temperature and moisture at 15 cm depth, ambient temperature and relative humidity. The period of analysis included two prairie growth seasons. Three models were considered for the statistical analyzes: i) tree cover on pasture productivity; ii) tree cover on microclimatic variables; and iii) the prairie productivity, considering the microclimatic variables as covariables. The results indicate that in the second growing season, the highest productivity was achieved with the tree-less treatment (0% cover). No effect of tree cover on the quality of the prairie was detected, nor on the microclimatic variables in either period. The microclimatic variables that best explained the development of the prairie were the minimum relative humidity and the ambient temperature. After two growing seasons, it is not possible to determine which treatment generates the best conditions for the productivity of the pasture, so it is necessary to continue with the measurements.